Jobs, Crime, and Votes: A Short-run Evaluation of the Refugee Crisis in Germany - Markus Gehrsitz; Martin Ungerer (Institute of Labor Economics (IZA), 2017)
Millions of refugees made their way to Europe between 2014 and 2015, with over one million arriving in Germany alone. Yet, little is known about the impact of this inflow on labor markets, crime, and voting behavior. This article uses administrative data on refugee allocation and provides an evaluation of the short-run consequences of the refugee inflow. Our identification strategy exploits that a scramble for accommodation determined the assignment of refugees to German counties resulting in exogeneous variations in the number of refugees per county within and across states. Our estimates suggest that migrants have not displaced native workers but have themselves struggled to find gainful employment. We find very small increases in crime in particular with respect to drug offenses and fare-dodging. Our analysis further suggests that counties which experience a larger influx see neither more nor less support for the main anti-immigrant party than counties which experience small migrant inflows.
Keywords: J6; J15; K4; D72; 330; immigration; refugees; unemployment; crime; voting